ANALISIS CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA SUB SEKTOR SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Miftahul Khoiri; Aulia Aulia (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to analyze the influence of the current ratio and debt to equity ratio on return on equity in Cement Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange. The population in this study are cement sub-sector companies listed on the Indonesia Stock Exchange. The sample used in this research is based on predetermined criteria, the number of agricultural sector companies listed on the Indonesia Stock Exchange in 2018 - 2023 that have met the criteria in sampling is 6 companies. The results of the partial analysis show that the Current Ratio has a partial positive and significant effect on the Return On Equity of cement sub-sector manufacturing companies listed on the Indonesia Stock Exchange. Debt to Equity Ratio has a positive and partially significant effect on Return On Equity of cement sub-sector manufacturing companies listed on the Indonesia Stock Exchange. Current Ratio and Debt to Equity Ratio simultaneously have a positive and significant effect on Return On Equity in cement sub-sector manufacturing companies listed on the Indonesia Stock Exchange.